Rio Fuego [large type] - Dundee, Wayne D. (Dundee, Wayne D. Lone McGantry western, 2025)
"Lone McGantry's journey to Rio Fuego, Colorado, began as a straightforward mission to acquire livestock for his burgeoning Nebraska horse ranch. However, destiny had other plans, thrusting him into a perilous showdown with a merciless mob hell-bent on lynching a prisoner en route to trial. In a desperate attempt to avert the lynching, tragedy strikes when the Rio Fuego marshal overseeing the prisoner's transfer is fatally shot, and the prisoner, Jaime, makes a daring escape. As Lone finds himself entangled with the late marshal's deputies and joining forces to restore order to the turbulent town, he swears to recapture the escaped prisoner and expose those accountable for the marshal's murder. Following a newfound lead suggesting Jaime's innocence, he embarks on an unrelenting pursuit, aided by the prisoner's resolute sister. Too bad their path takes them deep into the heart of New Mexico, where they're sure to face a barrage of challenges, from cunning bushwhackers to other menacing hazards."--